Detection of subgingival periodonto-pathogens and inflammaory cytokines in Malaysian adults with chronic periodontitis / Nursolehah Shahruddin - Nursolehah, Shahruddin (2019)
Objectives: In periodontitis, the interaction between lipopolysaccharide from gram-negative bacteria with host cells initiates the secretion of cytokines such as interleukin-1 (IL-1), interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α). The aim of this study was to assess the frequency of detection of subgingival microbiota Porphyromonas gingivalis (P. gingivalis), Tannerella forsythia (T. forsythia), Prevotella intermedia (P. intermedia) and Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) and the levels of IL6, IL-17, resistin and TNF-α among selected population of Malaysian chronic periodontitis (CP) subjects and to assess their association with periodontal parameters. Methods: A total of 167 CP and 134 healthy subjects were recruited. Visible plaque index (VPI), gingival bleeding index (GBI), probing pocket depths (PPD) and clinical attachment levels (CAL) were recorded. Subgingival plaque and blood were sampled from all subjects. Quantification of resistin, IL-17, IL-6 and TNF-ɑ was performed by ELISA. Real time PCR (qPCR) was used to frequency of detection and quantitate of P. gingivalis, T. forsythia, P. intermedia and A. actinomycetemcomitans. Results: Prevalence and mean counts of P. gingivalis, T. forsythia, P. intermedia and A. actinomycetemcomitans were higher in CP subjects [(94.50%, 24.66×105 cells/μl), (92.10%, 7.70×105 cells/μl), (72.60%, 6.61×105 cells/μl), (7.30%, 0.14×105 cells/μl) respectively] (p <0.05) compared to healthy controls [(73.70%, 8.32×105 cells/μl), (62.00%, 4.75×105 cells/μl), (58.40%, 5.17×105 cells/μl), (not determined (ND)) respectively]. Similarly level of resistin, IL-17, IL-6 and TNF-ɑ levels were higher in CP subjects [(100%, 274620 pg/ml), iv (100%, 727.13pg/ml), (100%, 26.84pg/ml), (100%, 54.91pg/ml) respectively] (p <0.001) compared to healthy controls ((94.90%, 22.12pg/ml), (45.30%, 0.19pg/ml), (30.70%, 0.006pg/ml), (ND) respectively). CP was found as the only confounder that influenced all clinical parameters, periodontal pathogens and inflammatory mediators. Additional confounders were CAL for P. gingivalis, PPD for T. forsythia and, VPI and CAL for IL-17. In the CP group, there was a positive but weak correlation between T. forsythia and IL-17 (r=0.189, p=0.016) and A. actinomycetemcomitans with TNF-α (r=0.166, p<0.033). Healthy group showed no significant correlation between periodontal pathogens and all inflammatory mediators. Conclusion: Adults with CP were found to have significantly higher prevalence and mean counts of P. gingivalis, T. forsythia, P. intermedia and A. actinomycetemcomitans and inflammatory mediators (resistin, IL-17, IL-6 and TNF-α) as compared to healthy controls. P. gingivalis was found to be positively associated with mean CAL while IL-17 was negatively associated with mean CAL. T. forsythia was positively associated with mean PPD. There was a weak but significant correlation between T. forsythia with IL-17 and A. actinomycetemcomitans with TNF-ɑ.